Molecular nutrition. - Patel, Vinood B. (Academic Press, an imprint of Elsevier, 2020)
Molecular Nutrition: Vitamins presents the nutritional and molecular aspects of vitamins with a specific focus on vitamins A, B1 (thiamine), B2 (riboflavin), B# (niacin), B5 (pantothenic acid), B6, (pyridoxine), B7 (biotin), B9 (folate), B12 (colbamin), C, D, E, and K. As part of the Molecular Nutrition series, this book discusses introductory aspects and general coverage of vitamins and nutrition, the molecular biology of the cell, including signaling, transporters, oxidative stress, receptors, uptake, immunity, proliferation, endoplasmic reticulum, differentiation, carcinogenesis and apoptosis. Final sections cover genetic machinery and its function, transcriptional processes, homeostasis genes, cancer, gene expression, mutations, and more. Emerging fields of molecular biology and important discoveries related to diet and nutritional health are also covered, rounding out the book. --